Pivotal role of glutathione depletion in eNOS uncoupling of LPS-Treated HUVECs - Chen, L.; Liu, E.; Cao, D.; Li, S.; Xiao, C.; Xiong, M.; Kou, Q. (Cellular and Molecular Biology, 2016)
The present study investigated the relationship between uncoupling of endothelial nitric oxide synthase (eNOS) and vascular endothelial cell (VEC) oxidative stress (OS) during sepsis and the role of eNOS glutathionylation in eNOS uncoupling of septic VECs. Human umbilical vein endothelial cells (HUVECs) cultured in vitro (EA.hy269 cell line) were incubated with Dulbecco's modified Eagle's medium (DMEM) (normal control group), lipopolysaccharide (LPS) (sepsis group), 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU) (glutathionylation group), and LPS+ dithiothreitol (DTT) (deglutathionylation sepsis group). As result, compared with the DMEM group, malondialdehyde (MDA) level and uncoupling eNOS activity significantly increased in the LPS and BCNU groups. However, in the LPS + DTT group, only the NO level increased. Compared with the LPS group, MDA level, NO concentration, and normal functional eNOS activity significantly decreased, and uncoupling eNOS activity significantly increased in the BCNU group. In the LPS + DTT group, MDA level and uncoupling eNOS activity significantly decreased, and NO concentration and normal functional eNOS activity significantly increased. During sepsis, the main mechanism for VEC OS was eNOS uncoupling mediated by eNOS glutathionylation.